Synthesis of Steered Flat-top Beam Pattern Using Evolutionary Algorithm - Mandal, D.; Kola, K. S.; Tewary, J.; Roy, V. P.; Bhattacharjee, A. K. (Advanced Electromagnetics, 2016)
In this paper a pattern synthesis method based on Evolutionary Algorithm is presented. A Flat-top beam pattern has been generated from a concentric ring array of isotropic elements by finding out the optimum set of elements amplitudes and phases using Differential Evolution algorithm. The said pattern is generated in three predefined azimuth planes instate of a single phi plane and also verified for a range of azimuth plane for the same optimum excitations. The main beam is steered to an elevation angle of 30 degree with lower peak SLL and ripple. Dynamic range ratio (DRR) is also being improved by eliminating the weakly excited array elements, which simplify the design complexity of feed networks.